Dekonstruksie van tradisionele probleem- realiteite: ’n Narratief-pastorale perspektief - J.J. de Jager; J.C. Muller (Hervormde teologiese studies, 2002)
Deconstruction of traditional problem realities: A narrative-pastoral perspective This article serves as an introduction to qualitative narrative research from a postmodern epistemological perspective. The research is directed at four pastoral-therapeutic processes and the stories told as part of those processes. Special focus is placed on the construction and deconstruction of problems in the fields of action: authority; typification; institutionalization. Perspectives regarding narrative, social constructionism, deconstruction and post-modern theology, are explained. The article positions itself in the practical research-processes.